Enhancing Elementary Buddhist Education: The Impact Of Visual And Auditory Multimedia Tools On Student Learning Outcomes - Hariyanto, Hariyanto; Khomaeni Hayatullah, Imam; Naval Ballesteros, Richard (Sekolah Pascasarjana Universitas Ibn Khaldun Bogor, 2025)
Multimedia-assisted learning represents a transformative strategy in modern education, designed to enhance student engagement and comprehension. This study investigates the impact of Buddhist-themed multimedia tools in elementary education, addressing limitations of traditional instructional methods. Using Dual Coding and Cognitive Load Theories as frameworks, a quasi-experimental pretest-posttest design compared the learning outcomes of students exposed to multimedia resources against those taught using conventional methods. The results demonstrated that integrating visual and auditory media significantly enhanced student comprehension, retention, and engagement. Statistical analyses, including t-tests and ANOVA, confirmed that the experimental group exhibited superior learning outcomes compared to the control group. Additionally, qualitative feedback indicated strong student approval of the interactive and culturally tailored content. However, challenges such as limited technological resources and insufficient teacher preparedness were identified, highlighting the necessity of targeted infrastructure investment and professional development. This study emphasizes the importance of culturally responsive multimedia tools in improving educational practices, offering practical recommendations for integrating innovative technologies into diverse learning environments